Does the form matter? Foreign capital inflows and economic growth in Ghana - Frank Adusah-Poku; William Bekoe (Economics and Econometrics Research Institute (EERI), 2018)
Empirically, results from time series and cross country studies have identified foreign capital inflows to play a pivotal role in the growth process of host countries. The goal of this article is to examine the impact of three of the four forms of foreign capital inflows (which include foreign aid, foreign direct investment and personal remittances) on economic growth in Ghana. The study employs the ARDL Bounds testing approach to cointegration on an annual time series data for Ghana from 1980-2012. The results of the study indicate that all the three forms of foreign capital inflows have positive and significant impacts on economic growth both in the short and long run. The results also show that of all the three forms of foreign capital inflows, foreign aid is the main driver of economic growth in Ghana both in the short and long run. The study recommends the design and implementation of good fiscal, monetary and trade policies to complement the flow foreign aid to the country for the realization of its full impact on growth.
Keywords: C1; F43; N17; 330; Economic growth; foreign capital inflows; ARDL; Ghana